Defense Spending as Strategic Investment in Indonesia: A Systematic Review of Governance and Capability Sustainability - Haridinuto; Surachman Surjaatmadja (Administratio, 2026)
Indonesia’s defense-spending problem cannot be understood only as a shortage of fiscal resources. It also reflects a governance-mediated capability risk: annual budget allocations, procurement decisions, sustainment obligations, manpower policy, industrial participation, and accountability mechanisms are not yet fully integrated into a long-cycle capability system.  This article examines the conditions under which defense spending in Indonesia may function as strategic investment rather than as a recurring fiscal burden. Strategic investment is understood here as expenditure that generates durable readiness, life-cycle affordability, industrial learning, strategic resilience, and public legitimacy.  The study employs a concept-driven systematic literature review using a PRISMA-informed protocol. Literature was identified through Scopus, Web of Science, and targeted Google Scholar searches, then screened and synthesized thematically. A final core corpus of 33 studies was analyzed across four themes: fiscal capacity and governance gap; life-cycle costing, procurement, and sustainment; defense manpower, reserve components, and budget efficiency; and industrial participation, accountability, and strategic value. The review finds that Indonesia’s central challenge is not merely underfunding, but capability leakage caused by weak alignment between fiscal planning, procurement continuity, sustainment costs, manpower design, industrial policy, and oversight.  Through the Defense Resource Governance and Management System framework, the article argues that defense spending becomes strategic investment only when it is governed as an integrated long-term capability system. The article concludes that failure to govern defense spending in this way is not simply an administrative inefficiency, but a national security risk because repeated expenditure may fail to accumulate durable strategic value.